A Systematic Literature Review on the Digitalization of Ethnomathematics in 101 Tower Taiwan - Agus Suyono; Lisnani Lisnani (Journal of Emerging Technologies in Ethnomathematics, 2025)
This study presents a systematic literature review exploring the integration of ethnomathematics in the context of the iconic Taipei 101 Tower through digitalization. The research aims to identify how mathematical concepts embedded in the cultural, architectural, and symbolic elements of the 101 Tower can be utilized in educational settings, particularly within the framework of digital learning tools. A total of 25 peer-reviewed articles published between 2013 and 2024 were selected using PRISMA methodology, focusing on keywords such as "ethnomathematics," "digitalization," "architecture," and "Taipei 101." The analysis reveals that the structure of the 101 Tower embodies rich mathematical patterns, including fractals, symmetry, proportions, and the Fibonacci sequence, all of which reflect Taiwanese culture and traditional beliefs. Furthermore, digital technologies—such as augmented reality (AR), virtual tours, and interactive apps—have enhanced students' engagement and understanding of these concepts. The study concludes that the digitalization of ethnomathematical elements of the 101 Tower has strong potential to foster culturally relevant mathematics education and promote global appreciation of local knowledge systems. This review contributes to the growing field of ethnomathematics by highlighting the relevance of cultural artifacts in mathematical education and interdisciplinary studies,